ANALISIS FAKTOR PAJAK DAN NON PAJAK TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study aims to analyze  tax factors and non tax factors that influence debt policy at manufacture company listed in the Indonesian Stock Exchange. The tax  factors in this study are taxes rate and earnings after taxes. And the non tax factors are operating leverages, sales growth, and  firms size. Period of research started from year of 2010-2013. This study used  purposive sampling method. The data analysis techniques used multiple linier regresion analysis. The results showed that  taxes rate has positive influence but not significant toward debt policy, Earning after taxes has negative influence and significant toward debt policy, Operating leverages has negative influence but not significant toward debt polict. While sales growth and firms size have positive influence  and significant toward debt policy.Keywords: Debt Policy, Taxes, Earning After Taxes, Operating Leverages, Sales Growth, and Firms Size